Investigação de componentes relacionados ao sistema endócrino vitamina D na próstata de ratos durante o envelhecimento - Gabriel Henrique Campolina Silva (2020)
A growing body of experimental and epidemiological evidence has addressed to the active metabolite of vitamin D, the 1α,25(OH)2D or calcitriol, a protective role against the development and progression of prostate cancer, a proliferative disorder that affects 1 in every 6 men over 65 years old. However, little is known about the distribution and putative age-dependent variation of vitamin D signaling related components in the prostatic tissue. Therefore, the present study aimed to characterize the expression pattern of the vitamin D receptor (VDR) and its heterodimeric partner RXR, as well as the key enzymes involved with the synthesis (CYP27B1) and degradation (CYP24A1) of calcitriol in the prostate, from adulthood to senility. By using an animal model that faithfully recapitulates the carcinogenesis process taking place in the prostate with advancing age and the combinatory implement of histological techniques, molecular biology and image analyses, we showed that the prostate is sensitive to calcitriol and capable to metabolize it locally, since both target enzymes and receptors were expressed at high levels in the glandular epithelium. However, as the animals aged, a drastic reduction in the number of positive cells and immunoreactivity for VDR, RXR, and CYP27B1 was detected in the prostatic tissue, occurring restricted to ducts and acini exhibiting atrophies, hyperplasia and metaplasias, as well as to those affected by premalignant lesions and adenocarcinomas. On the other hand, the CYP24A1 expression significantly increased with advancing age and remained sharply even in those histopathological altered areas. This intricate imbalance between the levels of CYP27B1 and CYP24A1 was associated with reduced bioavailability of calcitriol in the senile prostate, which in addition to decreased expression of VDR and RXR expression, further limits the classic anti-proliferative action mediated by vitamin D signaling in prostate cells. This evidence was corroborated by the increased proliferative activity at sites where the factors implicated with calcitriol synthesis and responsiveness had its expression inhibited. Taken together, our results highlight a set of modifications over the course of aging with a high potential to impair the protective effects of vitamin D signaling on the prostate, thereby favoring the arising of histopathological alterations that disturb tissue homeostasis and may even progress to cancer.